137k views
5 votes
2(5x + 3) - 2+1 = 70

2 Answers

4 votes

Answer:

2(5x + 3) - 2+1 = 70

10x + 6 - 2 + 1 = 70

10x + 7 - 2 = 70

10x + 5 -5 = 70 - 5

10x = 65

10/10x = 65/10

x = 6.5

Explanation:

2(5x + 3) - 2+1 = 70

10x + 6 - 2 + 1 = 70

10x + 7 - 2 = 70

10x + 5 -5 = 70 - 5

10x = 65

10/10x = 65/10

x = 6.5

User Mehrdad Khosravi
by
5.3k points
3 votes

Answer:

x = 13/5

OR

x = 2.6

Explanation:

Do the operations in the order BEDMAS (Brackets, exponents/roots, division/multiplication, addition/subtraction). Between each pair, like division/multiplication, the operations are not done in the order, but from left to right.

2(5x + 3) - 2 + 1 = 70 Distribute over brackets

10x + 6 - 2 + 1 = 70 Combine like terms

10x + 5 = 70 Subtract 5 from both sides.

10x = 65 Divide both sides by 10 to isolate x.

x = 65/10 Reduce to lowest terms by diving both numbers by 5.

x = 13/5 Answer as a fraction

x = 2.6 Answer in decimal form

If there was a bracket around (2+1) the answer would be 67/10.

User Sakthi
by
5.7k points